Beneficial electrophysiologic effects of sacubitril in different arrhythmia syndromes. (25th November 2020) - Frommeyer, G; Dimanski, D; Ellermann, C; Wolfes, J; Eckardt, L
Abstract: Background: Previous studies report conflicting data regarding anti- or proarrhythmic effects of sacubitril. The aim of the presents study was to assess the impact of sacubitril in different arrhythmia models. Methods and results: In 12 isolated rabbit hearts, sacubitril was infused in rising concentrations (3, 5, 10μM) after obtaining baseline data. In 12 further hearts, erythromycin was administered to simulate long QT syndrome-2 (LQT2). Other 12 hearts were perfused with veratridine to mimic long QT syndrome-3 (LQT3). Both LQT groups were treated with sacubitril (5μM). Ventricular vulnerability was assessed by a pacing protocol. AV-blocked bradycardic hearts were perfused with a hypokalemic solution to trigger torsade de pointes (TdP). In further 13 hearts, AF was induced by a combination of acetylcholine and isoproterenol (ACH/ISO) and sacubitril (5μM) was added afterwards. With sacubitril, action potential duration (APD) was abbreviated whereas spatial dispersion of repolarization (SDR) remained stable. In both LQT groups, APD and SDR were increased. Infusion of sacubitril reduced APD and SDR in the LQT2-group (APD: −21 ms, p<0.05; SDR: −8 ms, p=ns) and did not alter APD but reduced SDR in the LQT3-group (APD: +2 ms, p=ns; SDR: −9 ms, p<0.05). Ventricular vulnerability was not altered by sacubitril. No TdP were observed with sacubitril treatment or under baseline conditions in any group. Erythromycin provoked 43 episodes of TdP (p<0.05). Additional treatment with sacubitril significantly suppressed TdP (3 episodes, p<0.05). With veratridine, 16 episodes of TdP (p=0.07) occurred. Further treatment with sacubitril did not reduce TdP (10 episodes, p=ns) significantly. Infusion of ACH/ISO led to an increased inducibility of atrial fibrillation (31 vs. 7 episodes). Additional infusion of sacubitril increased atrial ERP (+21ms, p<0.05) and reduced inducibility of AF (9 episodes). Conclusion: Sacubitril abbreviated APD and was not proarrhythmic. SDR is a major pathomechanism of TdP and was reduced by sacubitril in both LQT groups. Thereby, sacubitril exhibits antiarrhythmic effects in LQT2 and may be beneficial in LQT3. Furthermore, sacubitril suppressed AF by prolonging aERP. Our results indicate beneficial effects of sacubitril on cardiac electrophysiology. Funding Acknowledgement: Type of funding source: None